1982
DOI: 10.1152/ajpheart.1982.242.1.h50
|View full text |Cite
|
Sign up to set email alerts
|

Fetal intestinal oxygen consumption at various levels of oxygenation

Abstract: In seven chronically catheterized fetal lambs, blood flow and oxygen consumption (VO2) in the combined small and large intestines were determined at various oxygen concentrations in fetal arterial blood (CaO2). Intestinal blood flow (Qi) was measured with the radioactive-microsphere technique; intestinal oxygen delivery (DO2 = Qi X CaO2), VO2 [Qi X C(a-v)O2, where oxygen extraction [C(a-v)O2/CaO2] were computed with the Fick equation. Compared with normally oxygenated fetuses (CaO2 greater than 6.6 ml/dl), mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 0 publications
5
27
1
Order By: Relevance
“…We have shown that severe hypoxemia in the newborn piglet causes significant decreases in stomach, small intestinal mucosa, and colon blood flow, as well as decreases in oxygen delivery and consumption. These results are consistent with those seen in the ovine fetus (7). These changes most likely reflect the compensatory routing of cardiac output to high priority organs (brain and heart) in the presence of hypoxemia, at the expense of low priority organs such as the GI tract (26,27).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…We have shown that severe hypoxemia in the newborn piglet causes significant decreases in stomach, small intestinal mucosa, and colon blood flow, as well as decreases in oxygen delivery and consumption. These results are consistent with those seen in the ovine fetus (7). These changes most likely reflect the compensatory routing of cardiac output to high priority organs (brain and heart) in the presence of hypoxemia, at the expense of low priority organs such as the GI tract (26,27).…”
Section: Discussionsupporting
confidence: 88%
“…100 g-I). Edelstone reported similar results in fetal lambs with CaOz 5 4.4 ml/dl (7). In four of seven of our animals, we noted a failure to meet oxidative demands when O2 delivery decreased below a critical level (~2 0 % of baseline values) or O2 extraction did not sufficiently increase (to 263% above baseline values).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…To date, 02 balance studies in animals and man have focused on normal, physiologic relationships,'-5 the acute pathophysiology of disease states,2' S1 or laboratory manipulations. [12][13][14][15][16][17][18][19][20] From the University of New Mexico School of Medicine, Departments of Pediatrics and Physiology, Albuquerque.…”
mentioning
confidence: 99%